Super-fine Valentine - Cosby, Bill, 1937- (Cosby, Bill, 1937- Little Bill books for beginning readers., 1998)
Little Bill makes a special Valentine for Mia but is reluctant to give it to her, because he is afraid that the other children in their third grade class will tease him.